Infrared and Raman studies on renal stones: the use of second derivative infrared spectra - Guerra López, José Rodolfo (2010)
Urolithiasis is a very frequent illness found in Argentina; however, stone analysis is not routinely performed. In this work, 86 renal calculi (from cities of Lujan and San Antonio de Areco, State of Buenos Aires, Argentina) have been analyzed by infrared and Raman spectroscopies, and the results correlated with the main possible pathological conditions. Calcium oxalate monohydrate (whewellite) and mixtures of calcium oxalate monohydrate and carbonate apatite were the most frequent compounds found in our samples. In order to improve the identification of different phases present in calculi [particularly whewellite and weddellite (calcium oxalate dihydrate)], the second derivative spectra were used. The FTIR spectroscopy together with the second derivative analysis provides the urologist with a good method for calculi component determinations.